2019
DOI: 10.3727/096504018x15344979253618
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Molecular Patterns of RET-Rearranged Lung Cancer in Chinese Patients

Abstract: RET rearrangement has been proven as an oncogenic driver in patients with lung cancer. However, the prevalence, clinical characteristics, molecular features and therapeutic options in RET-rearranged patients remain unclear, especially in Chinese lung cancers. We retrospectively collected 6125 Chinese lung cancer patients who have been profiled using next-generation sequencing (NGS). The clinical demographics and molecular features of RET rearrangement-positive patients were analyzed. RET rearrangements were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 36 publications
4
50
1
Order By: Relevance
“…Each of these studies included less than 20 patients with RET fusion-positive disease. Several larger studies have similarly described patients with RET fusions, but no comparison group was available [ 30 , 33 – 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each of these studies included less than 20 patients with RET fusion-positive disease. Several larger studies have similarly described patients with RET fusions, but no comparison group was available [ 30 , 33 – 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, Wang et al [39] reported that one unique mutational signature in Chinese patients with NSCLC is associated with an increasing EGFR mutation rate together with gene fusions, such as RET and ALK. In one retrospective analysis, concurrent EGFR mutations were found in 7 of 47 RET-rearranged adenocarcinomas [3]. In our study, patients with acquired RET-rearrangement after progression on EGFR TKIs were excluded due to the concern of the potential prognostic implications of frontline EGFR-TKI administration, and no co-existence of other driver-gene alteration appeared.…”
Section: Discussionmentioning
confidence: 92%
“…The dawn of the targeted therapy era saw the discovery of receptor tyrosine kinase RET fusion in 1-2% of nonsmall cell lung cancers (NSCLC) [1,2] and proved it to be tumorigenic and targetable. Regarding the tumorigenicity, although several studies reported the prevalence of concomitant genetic alterations based on a limited sample size [3][4][5][6], the effects of these concomitant alterations on clinical outcomes were scant.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al revealed that NORAD expression was elevated in pancreatic cancer tissues, and NORAD silencing impeded metastasis and epithelial-to mesenchymal-transition (EMT) of pancreatic cancer cells in vivo and in vitro [ 30 ]. Another research revealed that NORAD was upregulated in colorectal cancer tissues, and NORAD inhibition induced apoptosis and constrained invasion, migration, and proliferation of colorectal cancer cells [ 31 ]. Zhang et al stated that NORAD exhaustion constrained migration, proliferation, and accelerated apoptosis of PCa cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%